Ensign wasps (Hymenoptera: Evanioidea, Evaniidae) in the fauna of Russia, with description of a new Brachygaster Leach species from Tajikistan and Uzbekistan - Belokobylskij, S.a. (Zootaxa, 2019)
The Evaniidae from the Russian fauna is reviewed. Three ensign or hatchet wasp genera and species occur only in the European part of Russia (West of Urals Mountains): Brachygaster minutus (Olivier, 1791), Evania dimidiata Spinola, 1838, and Prosevania fuscipes (Illiger, 1807). Species were also recorded in the following countries for the first time: B. minutus in Abkhazia, Azerbaijan, Georgia, Kazakhstan, Kyrgyzstan and in the numerous localities of the European part of Russia; Evania dimidiata in North Caucasus of Russia (Dagestan); Prosevania fuscipes in Abkhazia. A new species with distinct sexual dimorphism, Brachygaster gussakovskiji sp. nov., is described from Tajikistan and Uzbekistan.